Risk factors for colorectal cancer in man induce aberrant crypt foci in rats: Preliminary findings. (2nd January 2016) - Yang, Kai; Fard, Sara; Furrer, Rudolf; Archer, Michael C.; Bruce, W. Robert; Lip, HoYin; Mehta, Rhea; O'Brien, Peter J.; Giacca, Adria; Ward, Wendy E.; Femia, A. Pietro; Caderni, Giovanna; et al.
ABSTRACT: Epidemiological studies have demonstrated clear associations between specific dietary and environmental risk factors and incidence of colorectal cancer, but the mechanisms responsible for these associations are not known. An animal model could facilitate such an understanding. Both genotoxic and nongenotoxic carcinogens induce aberrant crypt foci (ACF) in the colons of F344 rats. F344 rats were provided with diets that contained putative risk factors for CRC: low calcium and low vitamin D, high iron, high fructose, and decreased light (UV) exposure or a control diet for 14 wk. The rats were then assessed with biochemical measures and by topological examination for evidence of colon abnormalities. Circulating ionized calcium was decreased from 2.85 to 1.69 mmol/L, and ACF were increased from 0.7 to 13.6 lesions/colon (both P < 0.001). Rats exposed to the multiple environmental conditions associated with colon cancer, developed ACF similar to the heterogeneous or ill-defined ACF in the human colon. Heterogeneous ACF are the most frequently seen in humans and are also seen in rats shortly after exposure to the non-genotoxic colon carcinogen, dextransulfate sodium. The rodent model could be used to assess the pathways from diet and environment to colon cancer and to provide guidance for clinical studies.